Fluoride exposure and its potential health risk assessment through ingestion of food in the mica mining areas of Jharkhand, India. Issue 5 (3rd July 2022) - Giri, Soma; Singh, Abhay Kumar
Abstract: The study was taken up to assess the fluoride concentration in the plant and animal based food items (cereals, pulses, vegetables, milk, chicken, egg and fish) in the vicinity of mica mining areas of Jharkhand which is rich in fluoride bearing minerals like biotite, muscovite, apatite, etc. The highest fluoride concentrations were observed in the wheat and chicken samples amongst the plant and animal origin foods, respectively. The leafy vegetables accumulated higher fluoride content as compared to other vegetables. The estimated daily intake (EDI) exceeded the Provisional tolerable daily intake (PTDI) of fluoride of 0.04 mg/kg/day in some of the wheat and rice samples. For the assessment of non-carcinogenic risk of fluoride, Hazard Quotient (HQ) and Hazard Indices (HI) were calculated as per United States Environmental Protection Agency methodology. The HQ of wheat and rice were highest amongst all the food items and contributed about 69% of the total risk. The hazard index (HI) for the adult population in view of the content of fluoride in the food samples ranged from 0.409 to 3.04 considering all the locations. HI exceeded unity in 60% of the locations, indicating non-carcinogenic risk to the populace. Higher HIs were assessed in the locations under the influence of mica mining activities.